2021
DOI: 10.1108/jima-08-2019-0162
|View full text |Cite
|
Sign up to set email alerts
|

Impact of religiosity and branding on SMEs performance: does financial literacy play a role?

Abstract: Purpose This study aims to examine the relationship between religiosity and branding on small- and medium-scale enterprises (SMEs’) performance in Saudi Arabia. It also examines the mediating role of financial literacy on the relationship among Islamic religiosity, branding and SMEs’ performance. Design/methodology/approach This study adopts the purposive sampling technique in three major commercial cities, namely, Riyadh, Jeddah and Al-Qassim to sample 100 SMEs each, resulting in a total sampling of 300 SME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 79 publications
4
24
2
1
Order By: Relevance
“…This is because currently it is easier to obtain additional business capital from banks, and the government has even created a special business financing program for small entrepreneurs. However, the results of this study support the research by Wasiuzzaman & Nurdin (2019), Aysan, et al, (2016), , Basha, M. B., et al, (2021), Sabiu & Abduh, (2021), Alharbi, et al, (2021 found that the size of the company does not affect the decisions of MSMEs in Malaysia to apply for financing. The results of the regression analysis in table 4, show that religiosity has a sig value of 0.000 (significant at the 1% significance level) with a coefficient value of 0.119, this…”
Section: Resultssupporting
confidence: 84%
“…This is because currently it is easier to obtain additional business capital from banks, and the government has even created a special business financing program for small entrepreneurs. However, the results of this study support the research by Wasiuzzaman & Nurdin (2019), Aysan, et al, (2016), , Basha, M. B., et al, (2021), Sabiu & Abduh, (2021), Alharbi, et al, (2021 found that the size of the company does not affect the decisions of MSMEs in Malaysia to apply for financing. The results of the regression analysis in table 4, show that religiosity has a sig value of 0.000 (significant at the 1% significance level) with a coefficient value of 0.119, this…”
Section: Resultssupporting
confidence: 84%
“…Dinc et al [30] described the relationship between Islamic financial literacy customer attitudes towards Islamic banking products and services. Alharbi et al [31] explored the relationship between customer attitude and financial literacy from an Islamic perspective. Customer attitude also helps with financial risk management, insurance, and investment planning [32].…”
Section: Literacy On Islamic Financementioning
confidence: 99%
“…High literacy on Islamic finance can motivate customers' behavioural intention to use Islamic banking products and services [53]. Alharbi et al [31] highlighted that customers' greater knowledge about Islamic financial literacy can influence their behavioural intention to use Islamic banking services. Georgiadou and Nickerson [54] examined customer perception of Islamic banks in the United Arab Emirates and indicated that a higher perception of customer attitudes about ethical confidence and trust in the organisation can increase a customer's behavioural intention to use Islamic banking services.…”
Section: Mediating Effect Of Attitudementioning
confidence: 99%
“…The finding from this study also has proved that managers' religiosity has relationship with CSR practice. Religious orientation has a strong influence on business success (Alharbi et al, 2021;Desiyanti & Kassim, 2020). Firms that incorporate the Islamic ethical values such as truthfulness, tolerance, firmness and fairness are more encouraged to sacrifice, give up and spend their wealth on the needy society and community, while expected reward only from Allah.…”
Section: Resultsmentioning
confidence: 99%
“…CSR exercise may also be driven by various personal values and interests of individual managers, guided by their religiosity (Iguchi et al, 2021;Mazereeuw et al, 2014). Previous studies had shown that managers' religiosity plays an important role as contributing factor towards SMEs' performance such as in Saudi Arabia (Alharbi et al, 2021) and Indonesia (Desiyanti & Kassim, 2020). Moreover, Ghadas et al (2018) revealed that it is crucial for managers to include the religiosity aspect in their business in terms of CSR so that it can give the highest benefit to the society and increase organizational performance and reputation.…”
Section: Managers' Religiositymentioning
confidence: 99%